From Plate to Performance: The Impact of Diet on Exercise Performance and Recovery - Pograniczny, Mikołaj; Mielżyńska, Adrianna; Jańczyk , Natalia; Pacołta, Adrianna; Nalepka, Marcelina; Pochopień, Jakub; Walkowicz, Dawid; Jankowska, Marlena; Presak, Michał; Baran, Karolina (Quality in Sport, 2025)
Diet is a key and indispensable element in sports, influencing both physical performance and recovery processes. This paper analyzes the relationship between diet composition and its impact on athletic performance. Particular attention is given to the role of macronutrients (proteins, fats, and carbohydrates) as well as micronutrients and vitamins in optimizing the body’s performance. The influence of diet and physical activity on hormonal regulation in athletes is also discussed. In addition to natural food components, the paper examines the role of performance-enhancing supplements such as creatine, caffeine, and beetroot juice, as well as substances with potentially negative effects, such as alcohol. The article also includes a brief mention of supplementation in e-sports, highlighting the effects of caffeine, L-theanine, and polyphenols on focus and reaction time. Furthermore, special attention is devoted to vegan athletes, analyzing their specific nutritional needs and the crucial role of supplementation in preventing deficiencies and supporting performance. The importance of personalized diet and supplementation, tailored to individual body needs and the specifics of a given sport discipline, is emphasized.